Role models [videorecording (Blu-Ray)] - Rudd, Paul; Wain, David, 1969-; Marino, Ken, 1968-; Scott, Seann William; Banks, Elizabeth, 1974-; Lynch, Jane, 1960- (Universal Studios Home Entertainment, 2009)
Danny and Wheeler are two salesmen who trash a company truck while on an energy drink-fueled bender. Upon their arrest, the court gives them a choice - the two can either do hard time or serve 150 hours of community service in a mentorship program. After one day with the kids, however, jail doesn't look half bad. Once the center's ex-con director gives them an ultimatum, Danny and Wheeler are forced to tailor their brand of immature wisdom to their charges, Augie and Ronnie. And if they can just make it through probation without getting thrown in jail, the world's worst role models will prove that, sometimes, it takes a village idiot to raise a child.